Exploring the emotions of disadvantaged adolescents in the classroom: Development of the S2* emotion application - Bourgeois, Amanda; Carroll, Annemaree; Bower, Julie (Frontiers in Education, 2022)
In the present research, three phases were conducted to develop a real-time emotional measure (S2* Emotion Application) to examine the emotional experiences and causes for those emotions in disadvantaged Australian adolescents. In the first phase, data were collected from 412 Year 10 students (aged 14-15 years) to understand their emotional experiences in the classroom. Second, the S2* Emotion Application was developed and trialed based on the initial findings from the first phase and relevant literature. In the third phase, the S2* was utilized with participants (N = 81) from Year 10 Math and English classes over three time points during an academic term. Results revealed that the most frequent reports of emotions and cause for that emotion were: boredom caused by schoolwork; happiness caused by peers; happiness caused by self; and boredom caused by teacher. When emotions and causes were examined separately, the most frequent reported emotion was boredom and the most frequent reported cause for emotion was peers. This tool may be used in future studies to further investigate these real-time emotional experiences allowing researchers to build on theoretical frameworks and provide skills and resources to best support educators.